2022
DOI: 10.7150/ijbs.67203
|View full text |Cite
|
Sign up to set email alerts
|

The Different Immune Responses by Age Are due to the Ability of the Fetal Immune System to Secrete Primal Immunoglobulins Responding to Unexperienced Antigens

Abstract: Among numerous studies on coronavirus 2019 (COVID-19), we noted that the infection and mortality rates of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) increased with age and that fetuses known to be particularly susceptible to infection were better protected despite various mutations. Hence, we established the hypothesis that a new immune system exists that forms before birth and decreases with aging. Methods: To prove this hypothesis, we established new ex-vivo culture conditions simulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Autophagy has been extensively studied not only for its protective role in cell survival under stress but also in pathogen infection ( Pei et al., 2014 ). Viruses have developed various strategies to block autophagy or use autophagy for their own benefit; on the other hand, host cells use autophagy as a defense mechanism to inhibit viral replication or deliver the virus to the lysosomal compartment for elimination ( Ko et al., 2017 ; Lee et al., 2022 ). It has been reported that each coronavirus may interact with the autophagy pathway and its components in its own unique way.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been extensively studied not only for its protective role in cell survival under stress but also in pathogen infection ( Pei et al., 2014 ). Viruses have developed various strategies to block autophagy or use autophagy for their own benefit; on the other hand, host cells use autophagy as a defense mechanism to inhibit viral replication or deliver the virus to the lysosomal compartment for elimination ( Ko et al., 2017 ; Lee et al., 2022 ). It has been reported that each coronavirus may interact with the autophagy pathway and its components in its own unique way.…”
Section: Discussionmentioning
confidence: 99%
“…This system is called the immune defense system. The least useful mechanisms have been discarded and left the best is innate immunity, which has evolved now ( 13 ).…”
Section: Evolution Of the Immune Systemmentioning
confidence: 99%